Mullā ˁAbbūd Al-Karkhī (1861–1946), vernacular poet of early twentieth century Baghdad. Issue 2 (2nd September 2018) - Holes, Clive
ABSTRACT: Mullā ˁAbbūd Al-Karkhī (1861–1946) was a prominent vernacular poet of Iraq during the years of the British Mandate. He wrote entirely in the colloquial and his fiercely critical and highly satirical poetry deals mainly with the duplicity of the British, the social realities of the Iraq of his time, and his resentment of foreign intrusion in Iraq's affairs. Al-Karkhī was a staunch Iraqi nationalist who stands at the beginning of a line of other Iraqi vernacular poets who have been similarly critical of the political and social realities of the Iraq of their time, notably ˁAzīz ˁAlī (1911–95) and ˁAbbās Jījān (1951–).